Maslahah-Based Evaluation of Mandatory Halal Certification Policy for Street Vendors - Eko Nur Cahyo; Maharani Pradnya Paramita; Khurun’in Zahro’ (El-Barka Journal of Islamic Economics and Business, 2026)
This study analyzes the realization of maslahah in the implementation of Government Regulation No. 42 of 2024 concerning mandatory halal certification for street vendors in Blitar Regency. Enforced on October 17, 2024, the regulation aims to ensure halal product assurance, strengthen consumer protection, and support the sustainability of micro and small enterprises. The issue is significant as the policy directly affects informal economic actors who often face regulatory and administrative constraints. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews with street vendors and relevant stakeholders and supported by an analysis of regulatory documents and related literature. The analysis focuses on assessing whether the implementation of the regulation delivers public benefit (maslahah) while maintaining proportionality and legal fairness. The findings indicate that halal certification provides tangible legal and economic benefits, including increased consumer trust, improved sales turnover, expanded market access, and enhanced business legitimacy. The policy has been generally well accepted, particularly due to government facilitation through simplified procedures and the free self-declaration halal certification scheme. From the perspective of Islamic legal theory, the implementation of this regulation reflects maslahah dharuriyah, as it safeguards religious compliance (hifz al-din) and promotes economic welfare (hifz al-mal). This study highlights halal certification as a regulatory instrument aligned with the objectives of Islamic law (maqasid al-shari‘ah).